Theoretical Aspects of Semantics-Based Language Implementation - Nielson, Flemming (DAIMI Report Series, 1990)
The research summarised here concerns theoretical aspects involved in the implementation of programming languages directly from a description of their semantics. This involves a study of the subtasks abstract interpretation (a framework for program analysis), code generation and program transformation and the main aim has been to ensure the correctness of these subtasks.